Robot-assisted removal of the orbital tumor (from practice) - V. N. Pavlov; R. I. Safiullin; R. R. Bakiev; R. F. Gilmanova; M. F. Urmantsev (Опухоли головы и шеи)
The implementation of robotic surgery, in particular the da Vinci surgical system, is one of the biggest breakthroughs in surgery since the invention of anesthesia, and represents the most significant achievement in minimally invasive surgery of this decade. If the use of the da Vinchi robotic system in pelvic surgery has long been the gold standard, the use of this system in surgery of the base of the skull and sinuses is quite rare and is currently more experimental. Due to the lack of description in the domestic and foreign literature, it seems interesting to us to demonstrate the clinical observation of a patient with an orbital tumor.